Prefiksasi Bahasa Melayu-Tolitoli (BMTLI) pada Masyarakat di Kabupaten Tolitoli - Endang Puji Astuti Endang; Oktiva Herry Chandra (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The Malay-Tolitoli (BMTLI) language is unique, especially in the field of morphology. This study aims to determine the prefix and its application in Malay-Tolitoli (BMTLI). This research was conducted using a generative morphology study with a model developed by Halle, namely the IP model (Item and Process), with data derived from interviews and observations of native speakers. The results of this study indicate that in the Malay-Tolitoli (BMTLI) language, there is a derivation process in the use of the prefix "Ba-" where there is a change in word class that changes the noun into a verb, and adjectives become verbs. However, the derivation process does not occur between verbs and verbs. This study also shows that the prefix "ba-" is always followed by a derivative verb. The prefix "ta-" in Malay-Tolitoli (BMTLI) is always followed by a verb used to indicate passive sentences without changing the word class, and the use of the prefix "mo-" is always followed by a transitive verb, and the prefix "moba-" is always followed by an intransitive verb in its use without changing the word class. These two prefixes only show the meaning "ingin" (want).